Vicitims of Family Violence - Ramljak, Alija A. (Kriminalističke teme, 2002)
When defining family according to family law we can freely and clearly establish that family is union defined by law. When we highlight that, it emerges that family is under protection of society, actually state and her jurisdiction. Regardless of given formulation, as well as tendency that family is privacy of individual, members of marriage, must follow principles of legality and state as a whole. Ruts of violent behavior in family are very deep, and this is the concern of this work. In the late sixties of this century violent behavior in USA was 6% annual rate, which lead the FBI director (Mr. William Sessions) to pay full attention to this problem and to make it equal with terrorism, drug abuse and counter espionage..., and treats it as a crime of national priority. From the above it is clear that this violent behavior must be seriously investigated.